Developing mobile augmented reality in picture book for teaching English for young learners - Naajihah Mafruudloh; Finaty Ahsanah; K. Khoiriyah (Research and Development in Education (RaDEn), 2024)
An effective language and learning process must contain interactive, fun, challenging, motivating aspects and provide more space for students to develop their creativity and independence, according to students' talents and interests; thus, appropriate teaching media can be as assisting tools. When selecting media, you need to consider several things, namely learning objectives, effectiveness, easy to obtain, students, use, not rigid, cost, and quality. One of the developments in learning media that is currently still new is learning media using Augmented Reality. This research aims to develop Augmented Reality-based text book learning media for English language learning. Developing text-book media using an application with a barcode scanner on text-books. This application displays 4D images or animations that have sound and movement so that it will help students to understand English texts. The research method used is the research and development method (Research & Development) while the product development model used is the ADDIE model (Analysis, Design, Development, Implementation, & evaluation. After developemnt anf evalution phase, the findings reveals that the outcome of teaching material product is deemed highly valid and appropriate for teaching English to yong learners, especially for primary school in this research context, as it was supported by the result of validation phase with media experts, subject matter experts, and student trials. Additionally, reflecting on the result of this study, the pedagogical implications of this result discussed further in this research.